The Letters of Pliny Younger: Book X partial translation - administrative correspondence with Emperor Trajan - Rossi, Andrea L. D. O. C. [UNESP]; Binato, Claudia P. [UNESP] (Univ Do Vale Do Rio Dos Sinos, 2017)
This article aims to present a partial bilingual translation Latin/Portuguese of some of the correspondence between Emperor Trajan and Senator and Consul Pliny Younger. These correspondences are part of a complete work, divided into ten books, which have 368 letters in total. The reference basis with philological treatment is the translation and compilation presented by the Loeb Classical Library, under the coordination of W.M.L. Hutchinson, a Harvard University project. The methodology applied to this translation is the cultural translation. It is not intended here to make a philological analysis but only a partial availability of the source for the Brazilian academy. The Plinian Correspondence is not extensively studied in Brazil, although well known. Thus, the main purpose is to make part of this source available in order to disseminate and publicize texts to researchers who find the language a problem to access it.
Keywords: letters; Pliny Younger; Book X; Emperor Trajan; translation